2016
DOI: 10.1063/1.4967358
|View full text |Cite
|
Sign up to set email alerts
|

Atomization and merging of two Al and W wires driven by a 1 kA, 10 ns current pulse

Abstract: Possibility of preconditioning of wires in wire array Z-pinch loads by an auxiliary low-level current pulse was investigated in experiments with two aluminum or two polyimide-coated tungsten wires. It was found that the application of a 1 kA, 10 ns current pulse could convert all the length of the Al wires (1 cm long, 15 μm diameter) and ∼70% of length of the W wires (1 cm long, 15 μm diameter, 2 μm polyimide coating) into a gaseous state via ohmic heating. The expansion and merging of the wires, positioned at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…According to [178], the core expansion velocity at (d I/dt) av = 150 A/ns was (3-6) • 10 5 cm/s for bare wires made of Au, Cu, Ag, and Al and (0.4-1) • 10 5 cm/s for bare wires made of W, Mo, and Pt. Shi et al [19], Rousskikh et al [123], Zhao et al [172], Wu et al [173], [174], and Li et al [184] measured v core values similar to those reported in [168] and [178].…”
Section: B Core Structure (Core Expansion and Stratification And Micr...supporting
confidence: 57%
See 4 more Smart Citations
“…According to [178], the core expansion velocity at (d I/dt) av = 150 A/ns was (3-6) • 10 5 cm/s for bare wires made of Au, Cu, Ag, and Al and (0.4-1) • 10 5 cm/s for bare wires made of W, Mo, and Pt. Shi et al [19], Rousskikh et al [123], Zhao et al [172], Wu et al [173], [174], and Li et al [184] measured v core values similar to those reported in [168] and [178].…”
Section: B Core Structure (Core Expansion and Stratification And Micr...supporting
confidence: 57%
“…However, in these cases, the intrinsic impedance of the driver became comparable to the resistance of the exploded wire, and the actual rate of the wire current is decreased. For instance, Wu et al [174] report that for (d I/dt) av = 100 A/ns, the rate of the current in an exploded 13-μm tungsten wire was 47 A/s. Sarkisov et al [94], [152], [176]- [179] proposed a driver for WE experiments which combines an off-the-shelf voltage pulse generator capable of producing nanosecond-rise time currents and a segment of coaxial cable.…”
Section: Experimental Arrangements For Studying the We In Vacuummentioning
confidence: 99%
See 3 more Smart Citations